(untitled) (Al-Academy, 2017)
Enjoy cinema privileged position , they have the ability to influence and the impact of including environs of prior art , and what distinguishes them , possessing motion picture , especially since the film possesses through its means technical ( camera , lighting, sound, editing , costume, scenery and makeup ) that work together in harmony and harmony to create enchanting fantasy world does not exist only in the imagination of corrupt officials . Out of imagination found that the art of make-up one of the means that enable it to create characters imagined located between simulate realistic characters (such manifestations of blood , cut leg, wounds , burns , etc. ..) and the figures are unrealistic , particularly in the creation of characters oddly shaped unfamiliar may be beautiful or ugly or scary , and so by employing tools and materials (such as powders , and plastics and pigments, and colors , and gum alcoholic or plastic ) to transform the features of Representative in whole or in part to the features may be animal or teratogenic or Nothingness her resemblance to the ground. The make-up is the work of the two leads , namely: Beauty cosmetic any personal or Taqbihaa , and other graphical zoom through personal profiles or minimized , while the bulk of the expressive side , is to create oddly shaped figures unfamiliar in virtual reality. I’ve included four chapters search included the first chapter , which explained the methodological framework of the research problem by asking the following: ( Can make-up that creates exotic figures in virtual reality). The second chapter dealt with the theoretical framework comprised three sections The first topic I talked about : the concept of exoticism The second topic was : make-up in the cinema. The third topic was : ( make-up building in the form of personal exoticism) The third chapter meant actions taken to search across indicators theoretical framework tool for the analysis of the film ( a Caribbean pirate). The fourth chapter included the results and the most important:- The use of make-up in the film Orwellian work to achieve the desired result through a change in the form of personal familiar to the unfamiliar figure in virtual reality -:The most important 2.The work of make-up to create a personal form of absurdly helped create suspense and surprise element in the film , and achieved success in the broad public demand it to pursue these kinds of movies In the end, research came the summary in English.